Carbonation resistance of recycled aggregate concrete. (20th April 2019) - Leemann, Andreas; Loser, Roman
Highlights: The moisture state of RA before concrete production has no impact on carbonation. Carbonated or porous RA can lead to an increase of carbonation coefficient K . Carbonation coefficient K of RC decreases with decreasing clinker content of the cement. Accelerated carbonation of RC provides a good assessment of natural carbonation. Abstract: The environmental impact of concrete production can be decreased by the use of cement with reduced clinker content or the reuse of concrete waste provided by the demolition of buildings in recycled aggregate concrete (RC). In this study, the carbonation resistance of RC is investigated in order to clarify the influence of recycled aggregate percentage, moisture state of the aggregates prior to concrete production and type of cement used. RC with two different replacement levels of natural aggregates is produced using three different blended cements and compared to reference concrete mixtures produced with natural aggregates. The carbonation resistance of RC can be decreased by particles of recycled aggregate that are either very porous or already carbonated before concrete production. There were no systematic differences in compressive strength and carbonation resistance between dry and pre-saturated aggregates. The carbonation resistance at a given compressive strength decreases with decreasing clinker content of the cement.